1992
DOI: 10.1021/j100197a047
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of polyoxycation species into conducting layered host lattices of molybdenum trioxide and tantalum disulfide

Abstract: Strukul, G.; (7) Mazzocchia. C.: Temuesti. E.; Gronchi, P.; Giuffre, L.; Zanderighi, L.Zanderighi, L. J. Coral. 1985, 96, 106. J . i.aia/. 1988, iii, 345. * (8) Guglielminotti, E. J. Caral. 1989, 120, 287. (9) Yashitake. H.; Iwasawa, Y., to be published. (IO) Yashitake, H.; Iwasawa, Y., to be published. (11) Sayers, D. A.; Stern, E. A,; Lytle, F. W. Phys. Rev. Lett. 1971, 35, (12) Oyanagi, H.; Matsushita, T.; Ito, M.; Kuroda, H. KEK Rep. 1984, (13) Kasugi, N.; Kuroda, H. Program EXAFS2; Research Center for -20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Several groups, particularly those of Chianelli, Frindt, Nazar, Fuentes, Curtis, and Wypych have exfoliated Li x MoS 2 in H 2 O to form a restacked MoS 2 , usually with surface areas of 10 m 2 /g but occasionally as high as 50 m 2 /g and much higher than the 5−6 m 2 /g MoS 2 obtainable from commercial vendors. Several reports, ,, particularly those of Nazar, have appeared recently on the subject of pillared layered chalcogenides as well. Not until the preparation of this paper had intercalated chalcogenides been tested for hydrodesulfurization activity, however.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups, particularly those of Chianelli, Frindt, Nazar, Fuentes, Curtis, and Wypych have exfoliated Li x MoS 2 in H 2 O to form a restacked MoS 2 , usually with surface areas of 10 m 2 /g but occasionally as high as 50 m 2 /g and much higher than the 5−6 m 2 /g MoS 2 obtainable from commercial vendors. Several reports, ,, particularly those of Nazar, have appeared recently on the subject of pillared layered chalcogenides as well. Not until the preparation of this paper had intercalated chalcogenides been tested for hydrodesulfurization activity, however.…”
Section: Introductionmentioning
confidence: 99%
“…CP/MAS spectra15 were recorded with a single contact, a contact time of 500 ms, a 'H 90°p ulse of 3.4 ms, a recycle delay of 5 where yA! and yH denote the gyromagnetic ratios of 27A1 and 'H and B is the radio-frequency field strength.…”
Section: Methodsmentioning
confidence: 99%
“…However, 6-coordinated Al in solid Al)3 can be observed by MAS NMR. The intensity ratio of the lines from 6-and 4-coordinated Al is often different from the expected value of 12, which may be due to the radio-frequency pulse-width effect or the relative populations of the sites.2 4 The resonance at 0 ppm is a composite containing a peak from the monomeric A1(H20)63+ cation and a line from at least one other 6-coordinated species.2 5 Elemental analysis and measurements of the cation-exchange capacity have shown that the effective charge of the guest species in clays is lower than the nominal value of 7+, and it has been proposed that the actual charge is 4+i4,9,10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the Cllayer anions can be replaced by tetrahedral anionic groups, e.g., [Fe(CO)4f- [242]. Guest compounds used for this purpose have been, e.g., metal cluster ions [246], metal complex ions with large ligands [247], polyoxometallates [248,249], the tubular alumino silicate imogolite ( Figure 22) [250]. A different approach is the insertion of isometric guest species with large diameter into layered host lattices, which are immobilized by secondary reactions.…”
Section: Synthesis and Intracrystalline Reactionsmentioning
confidence: 99%